(untitled) (Experimental biology, 2015)
It was comparatively studied of the liver of a lake frog from waters of the Ile-Balkhash Basin: Kapchagay and Kurti reservoir storages and wastewater collector reservoir - Sorbulak. Morphological changes in the liver of a chronic nature in the form of proliferation of connective tissue, endothelial desquamation, fi brosis and infl ammatory infi ltrates are caused by unfavorable situation in the studied reservoirs. The presence of binucleated cells was accompanied by the occurrence of a large number of liver melano-macrophages centers. All this testifi es about the dynamic process of regeneration in the liver. Morphological studies also has revealed the changes of the compensatory-adaptive nature and pathological reactions of varying severity.